Automation Reformation Scheme of High-water Filling System of Coal Mine - HOU Jin-jing; ZHANG You-ming; LI Zhi-feng (Gong-kuang zidonghua, 2012)
The paper introduced main content, implementation of automatic control and technical difficulties of automation reformation of high-water filling system of coal mine, focused on implementation of automatic control of water-filled test tube, pulp and filling, and water washing pipe, and gave solutions of technical problems of level measurement, flow measurement, and pressure measurement. The reformed system can greatly improve filling quality and save labor costs, which has high promotional value.